Nano composite material with good water dispersibility and X-ray radiation luminescence property and preparation method thereof
By modifying the surface of halloysite nanotubes and hydrothermal reaction, nanoparticles are grown, which solves the problems of toxic metal elements in existing X-ray radioluminescent materials and non-environmental protection of the preparation process, and achieves good water dispersion of nanocomposites. and X-ray radioluminescence properties.
Patent Information
- Application Number
- CN202411408895.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-24
AI Technical Summary
Existing X-ray luminescent materials have problems such as toxic metal elements, unenvironmental preparation technology, large particle size and difficulty in obtaining good water dispersion.
By using the surface modification and water heating reaction of Ellow nano -pipe, anchor the EDTA group and grow nanoparticles on its surface to prepare nano -composite materials with good water decentralization and X -ray radiation.
It achieves good water dispersion of nanocomposites, controls the size at the nano-micro level, does not contain highly toxic metal elements, and the preparation process is environmentally friendly.
Smart Images

Figure CN119351103A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a nano composite material with radiation luminescence performance and a preparation method thereof, and more specifically, to a nano composite material with good water dispersibility and X-ray radiation luminescence performance and a preparation method thereof. Background Art
[0002] X-rays are a type of high-energy electromagnetic waves that have broad application prospects in the fields of medical testing, radiotherapy, metal flaw detection, aerospace, and device testing. In the above applications, X-ray scintillator materials play a core role. X-ray scintillator materials are special materials that can convert X-rays into visible light or near-visible light. Their special photophysical properties and huge commercial value continue to attract the research interests of manufacturers and scientists around the world.
[0003] It should be noted that the existing X-ray imaging technology mainly relies on rigid X-ray scintillator material screens to achieve the transformation of X-rays to visual images, but the imaging quality of this type of scintillator material screens for non-planar objects is poor, and it is even more difficult to achieve dynamic imaging on non-planar objects. Therefore, the research work on flexible X-ray scintillator material screens has received widespread attention from scholars in related fields in recent years. The ideal flexible screen is expected to be processed into any desired shape to fit or adapt to non-planar objects, which is conducive to meeting the needs of dynamic real-time monitoring. Existing X-ray scintillator materials can be divided into organic X-ray scintillator materials and inorganic X-ray scintillator materials according to their chemical composition. Organic scintillator materials are often composed of elements with small atomic radii, which leads to limited absorption of X-rays by organic scintillator materials and inability to obtain good radioluminescence performance. Although inorganic scintillator materials have good radioluminescence performance, inorganic scintillator materials are currently mainly crystalline materials, which are difficult to process into flexible devices, and the preparation and processing process relies on high-temperature treatment or organic solvent evaporation, which is difficult to meet the development concept of "green chemistry".
[0004] Patent CN 118407136 discloses a lead-based organic-inorganic hybrid single crystal scintillator material and its preparation method and application. The lead-based organic-inorganic hybrid single crystal scintillator has a chemical formula: Bmpip2PbBr4, which can convert radiation signals such as X-rays, gamma rays, alpha ions and neutrons into visible light and near-visible light, and has good radioluminescence performance, but the material involves the highly toxic Pd element, and the preparation process uses a solvent evaporation method that has a heavy burden on the environment.
[0005] Patent CN 118027968 discloses a Bi 3+ and Eu 3+Ion co-doped Y2MgTiO6 phosphor can be effectively excited by X-rays and emit visible light with a wavelength in the range of 550 to 650 nm. The phosphor has good thermal stability and low preparation cost. However, the product phosphor cannot obtain good water dispersibility and is difficult to further process into flexible materials.
[0006] Patent CN 117304216 discloses an X-ray scintillator material based on rare earth metal halides and a preparation method thereof, which mainly comprises mixing piperidine compounds, rare earth metal halides, alcohol substances, and hydrogen halide solutions to obtain a precursor solution, and further mixing an anti-solvent with the precursor solution to obtain a radioluminescent X-ray scintillator material. However, the particle size of this type of scintillator material is large, and it is difficult to obtain good water dispersibility and further process it into a flexible material.
[0007] It can be seen that the X-ray radiation luminescent materials reported above have the problems of containing toxic metal elements, the preparation process is not environmentally friendly, the particle size is large and it is difficult to obtain good water dispersibility. Therefore, the preparation and development of an X-ray scintillator material with low toxicity, good water dispersibility and particle size controllable at the nano-micro scale has become the focus and difficulty of research in this field. Summary of the invention
[0008] The purpose of the present invention is to provide a nanocomposite material with good water dispersibility and X-ray radiation luminescence performance and a preparation method thereof, so as to solve the problems existing in traditional X-ray radiation luminescence materials, such as containing toxic metal elements, environmentally unfriendly preparation process, large particle size and difficulty in obtaining good water dispersibility.
[0009] The object of the invention is achieved in this way: A method for preparing a nanocomposite material having good water dispersibility and X-ray radiation luminescence performance comprises the following steps: (1) Take halloysite nanotubes, add them into water to form a nanosuspension, then add disodium ethylenediaminetetraacetate (EDTA-2Na), 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCl), 1-hydroxybenzotriazole (HOBT) and N,N-diisopropylethylamine, stir and react for a certain period of time, perform the first centrifugation, discard the lower precipitate, take the upper suspension, and then perform the second centrifugation, collect the precipitate, and dry under reduced pressure to obtain the modified halloysite nanotubes.
[0010] (2) The modified halloysite nanotubes obtained in step (1) are added to water to form a nanosuspension, and then sodium nitrate, yttrium nitrate hexahydrate, praseodymium nitrate hexahydrate and ammonium fluoride are added, and the pH value is adjusted to weak acidity using nitric acid. The aqueous solution is transferred to a hydrothermal synthesis reactor, heated for a certain period of time, cooled to room temperature, and the precipitate is collected by centrifugation and dried under reduced pressure to obtain the nanocomposite material.
[0011] Furthermore, in step (1), the length of the halloysite nanotube is 200-2000 nm, preferably 200-1000 nm, more preferably 200-500 nm; the inner diameter is 10-100 nm, preferably 20-50 nm.
[0012] Furthermore, in step (1), the mass ratio of EDTA-2Na to halloysite nanotubes is (0.5-4):1, preferably (1-2):1.
[0013] Furthermore, in step (1), the mass ratio of EDCl to halloysite nanotubes is (0.5-4):1, preferably (1-2):1.
[0014] Furthermore, in step (1), the mass ratio of HOBT to halloysite nanotubes is (0.5-4):1, preferably (0.5-1.5):1.
[0015] Furthermore, in step (1), the mass ratio of N,N-diisopropylethylamine to halloysite nanotubes is (0.5-4):1, preferably (0.5-1.5):1.
[0016] Furthermore, in step (1), the reaction time is 24 to 72 hours, preferably 36 to 60 hours.
[0017] Furthermore, in step (1), the first centrifugation speed is 500-2000 rpm, and the second centrifugation speed is 5000-8000 rpm.
[0018] Furthermore, in step (2), the mass ratio of sodium nitrate to modified halloysite nanotubes is (0.2-2):1, preferably (0.4-1):1.
[0019] Furthermore, in step (2), the mass ratio of yttrium nitrate hexahydrate to modified halloysite nanotubes is (1-5):1, preferably (2-4):1.
[0020] Furthermore, in step (2), the mass ratio of praseodymium nitrate hexahydrate to modified halloysite nanotubes is (0.1-0.5):1, preferably (0.2-0.4):1.
[0021] Furthermore, in step (2), the mass ratio of ammonium fluoride to halloysite nanotubes is (0.5-3):1, preferably (0.8-2):1.
[0022] Furthermore, in step (2), the pH value is 4 to 6, preferably 4.5 to 5.5.
[0023] Furthermore, in step (2), the hydrothermal reaction temperature is 150-200°C, preferably 170-190°C.
[0024] The invention utilizes the condensation reaction between the surface hydroxyl group of halloysite nanotubes and the carboxyl group in EDTA-2Na, anchors the EDTA group in the surface structure of the halloysite nanotubes through a one-step chemical reaction, then mixes the EDTA-modified halloysite nanotubes with yttrium nitrate hexahydrate, praseodymium nitrate hexahydrate and ammonium fluoride through a hydrothermal reaction, in-situ grows nanoparticles with X-ray radiation luminescence performance on the surface of the halloysite nanotubes, and further obtains a nanocomposite material with good water dispersibility and X-ray radiation luminescence performance.
[0025] The nanocomposite material prepared by the present invention has the advantages of good water dispersibility, size control at the nano-micro level, and no high-toxic metal elements such as Pd.
[0026] The entire preparation process of the present invention uses water as a reaction solvent, which has the advantage of being green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the synthesis route of the nanocomposite material in Example 1.
[0028] Among them, A) is the roadmap of step (1), and B) is the roadmap of step (2).
[0029] Figure 2 This is a photograph of the uniform dispersion of the nanocomposite material prepared in Example 1 in water.
[0030] Figure 3 The thermogravimetric analysis diagram of EDTA-modified halloysite nanotubes (HNTs-EDTA) and halloysite nanotubes (HNTs) in Example 1.
[0031] Figure 4 This is the X-ray photoelectron spectrum of the nanocomposite material prepared in Example 1.
[0032] Figure 5 This is a local enlarged view of the C1s signal peak area in the X-ray photoelectron spectrum of the nanocomposite material prepared in Example 1.
[0033] Figure 6 This is a local enlarged view of the Pr 3d signal peak area in the X-ray photoelectron spectrum of the nanocomposite material prepared in Example 1.
[0034] Figure 7 This is a high-resolution transmission electron microscopy element distribution map of the nanocomposite material prepared in Example 1.
[0035] Figure 8 This is a high-resolution transmission electron microscope high-angle annular dark field image of the nanocomposite material prepared in Example 1.
[0036] Fig. 9 This is the X-ray excited fluorescence spectrum of the nanocomposite material prepared in Example 1. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with the examples. The following examples are only for illustration and do not limit the scope of protection of the present invention in any way. The processes and methods not described in detail in the following examples are conventional methods known in the art. The raw materials or reagents used in the examples can be purchased through commercial channels. Among them, halloysite nanotubes were purchased from Guangzhou Xinxi Metallurgical Chemical Co., Ltd., 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDCl), 1-hydroxybenzotriazole (HOBT) and N,N-diisopropylethylamine were purchased from Beijing Bailingwei Technology Co., Ltd. with a purity of 98%. Disodium ethylenediaminetetraacetate (EDTA-2Na) was purchased from Shanghai McLean Biotechnology Co., Ltd. with a purity of 98%. Sodium nitrate and yttrium nitrate hexahydrate were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a purity of 99.9%. Praseodymium nitrate hexahydrate was purchased from 3A Chemical Co., Ltd., USA, with a purity of 99.9%. Ammonium fluoride was purchased from Shanghai McLean Biotechnology Co., Ltd. with a purity of 98%. The water used in the preparation process is Wahaha purified water. The same results can be obtained by using the same reagents from other sources.
[0038] Example 1: HNTs@NaYF4:Pr 3+ Preparation of nanocomposites 1.0 g of halloysite nanotubes was added to 10 mL of water to prepare a nanosuspension, and then 1.25 g of disodium ethylenediaminetetraacetate (EDTA-2Na), 1.2 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCl), 0.8 g of 1-hydroxybenzotriazole (HOBT) and 0.8 g of N,N-diisopropylethylamine were added. After stirring at room temperature for 48 hours, the mixture was centrifuged at 1000 rpm for 3 minutes, the lower precipitate was discarded, the upper suspension was taken, centrifuged at 7000 rpm for 3 minutes, the precipitate was collected, and dried under reduced pressure to obtain EDTA-modified halloysite nanotubes (HNTs-EDTA).
[0039] Take 1.0 g HNTs-EDTA and add it to water to prepare a nanosuspension, then add 0.5 g sodium nitrate, 2.0 g yttrium nitrate hexahydrate, 0.4 g praseodymium nitrate hexahydrate and 0.85 g ammonium fluoride, and use nitric acid to adjust the pH value to 5.0. The above aqueous solution was transferred to a hydrothermal synthesis reactor, heated at 180 ° C for 24 hours, cooled to room temperature, centrifuged at 7000 rpm to collect the precipitate, and dried under reduced pressure to obtain the product HNTs@NaYF4:Pr 3+ Nanocomposite materials.
[0040] like Figure 2 As shown, the nanocomposite material prepared in Example 1 can be uniformly dispersed in water, indicating that the material has good water dispersibility.
[0041] Example 2: HNTs@NaYF4:Pr 3+ Preparation of nanocomposites 1.0 g of halloysite nanotubes was added to 10 mL of water to prepare a nanosuspension, and then 1.25 g of disodium ethylenediaminetetraacetate (EDTA-2Na), 1.2 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCl), 0.8 g of 1-hydroxybenzotriazole (HOBT) and 0.8 g of N,N-diisopropylethylamine were added. After stirring at room temperature for 48 hours, the mixture was centrifuged at 1000 rpm for 3 minutes, the lower precipitate was discarded, the upper suspension was taken, centrifuged at 7000 rpm for 3 minutes, the precipitate was collected, and dried under reduced pressure to obtain EDTA-modified halloysite nanotubes (HNTs-EDTA).
[0042] Take 1.0 g HNTs-EDTA and add it to water to prepare a nanosuspension, then add 0.5 g sodium nitrate, 2.0 g yttrium nitrate hexahydrate, 0.3 g praseodymium nitrate hexahydrate and 0.85 g ammonium fluoride, and use nitric acid to adjust the pH value to 5.0. The above aqueous solution was transferred to a hydrothermal synthesis reactor, heated at 180 ° C for 24 hours, cooled to room temperature, centrifuged at 7000 rpm to collect the precipitate, and dried under reduced pressure to obtain the product HNTs@NaYF4:Pr 3+ Nanocomposite materials.
[0043] Example 3: HNTs@NaYF4:Pr 3+ Preparation of nanocomposites 1.0 g of halloysite nanotubes was added to 10 mL of water to prepare a nanosuspension, and then 1.25 g of disodium ethylenediaminetetraacetate (EDTA-2Na), 1.2 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCl), 0.8 g of 1-hydroxybenzotriazole (HOBT) and 0.8 g of N,N-diisopropylethylamine were added. After stirring at room temperature for 48 hours, the mixture was centrifuged at 1000 rpm for 3 minutes, the lower precipitate was discarded, the upper suspension was taken, centrifuged at 7000 rpm for 3 minutes, the precipitate was collected, and dried under reduced pressure to obtain EDTA-modified halloysite nanotubes (HNTs-EDTA).
[0044] Take 1.0 g HNTs-EDTA and add it to water to prepare a nanosuspension, then add 0.5 g sodium nitrate, 2.0 g yttrium nitrate hexahydrate, 0.2 g praseodymium nitrate hexahydrate and 0.85 g ammonium fluoride, and use nitric acid to adjust the pH value to 5.0. The above aqueous solution was transferred to a hydrothermal synthesis reactor, heated at 180 ° C for 24 hours, cooled to room temperature, centrifuged at 7000 rpm to collect the precipitate, and dried under reduced pressure to obtain the product HNTs@NaYF4:Pr 3+ Nanocomposite materials.
[0045] Example 4: HNTs@NaYF4:Pr 3+ Preparation of nanocomposites Take 1.0 g of halloysite nanotubes, add 10 mL of water to prepare a nanosuspension, then add 1.25 g of ethylenediaminetetraacetic acid disodium (EDTA-2Na), 1.2 g of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDCl), 0.8 g of 1-hydroxybenzotriazole (HOBT) and 0.8 g of N,N-diisopropylethylamine, stir at room temperature for 48 hours, and then centrifuge. Centrifuge for the first time at 1000 rpm for 3 minutes, discard the lower precipitate, take the upper suspension, centrifuge for the second time at 7000 rpm for 3 minutes, collect the precipitate, and dry under reduced pressure to obtain EDTA-modified halloysite nanotubes (HNTs-EDTA).
[0046] Take 1.0 g HNTs-EDTA and add it to water to prepare a nanosuspension, then add 0.5 g sodium nitrate, 2.0 g yttrium nitrate hexahydrate, 0.4 g praseodymium nitrate hexahydrate and 0.85 g ammonium fluoride, and use nitric acid to adjust the pH value to 3.0. Transfer the above aqueous solution to a hydrothermal synthesis reactor, heat at 180°C for 24 hours, and then cool to room temperature.
[0047] The product is a brown hard block that cannot be dispersed in water.
[0048] The above-prepared products were subjected to the following structural characterization and performance tests.
[0049] (1) Thermogravimetric analysis characterization The samples were thermally analyzed using a Pyris 6 thermogravimetric analyzer. A heating program was set from room temperature to 750 °C at a heating rate of 10 °C / min, and the nitrogen flow rate was 20 mL / min. Figure 3 The thermogravimetric analysis diagram of EDTA-modified halloysite nanotubes (HNTs-EDTA) and halloysite nanotubes (HNTs) in Example 1.
[0050] In the initial stage of thermal orientation, both HNTs-EDTA and HNTs lose weight, which is caused by the evaporation of the crystalline water adsorbed on the surface, lumen and curled layers of HNTs. Figure 3 The thermal weight loss phenomenon in the middle part is caused by the dehydration condensation reaction of a small amount of organic components and hydroxyl groups. Figure 3 As shown in the figure, the thermogravimetric curve of the modified HNTs-EDTA is significantly different from that of HNTs. Compared with the thermogravimetric curve of HNTs, the thermogravimetric curve of HNTs-EDTA has a more obvious thermal weight loss phenomenon in the middle, and the final mass percentage at 750°C is also significantly smaller than that of HNTs. This shows that in the EDTA-modified halloysite nanotubes, the organic component accounts for a larger proportion and eventually thermally decomposes at high temperatures. The above results show that through the first step of the modification reaction, the EDTA group has been successfully modified on the surface of the halloysite nanotubes.
[0051] (2) X-ray photoelectron spectroscopy characterization The nanocomposite sample in Example 1 was analyzed using an American Thermo Scientific ESCALAB 250Xi X-ray photoelectron spectrometer. The monochromatic Kα line of the Al target was used as the radiation source, and the vacuum degree of the analyzer was 3×10 -10 MPa, with the 1s orbital spectrum of carbon (peak at 286 eV) as reference. The signal peaks of the basic elements constituting the original HNTs, such as Si 2p and Al2p, can be found at Figure 4 The Na 1s, O 1s, F 1s and Y 3d signal peaks are also clearly visible. Figure 5 There are two signal peaks at 289.5 and 285.5 in the C 1s peak, which is consistent with the chemical composition of the EDTA structural unit with the coexistence of alkyl carbon and carbonyl carbon. Figure 6 The Pr 3d signal can be clearly observed, proving the existence of the luminescent center Pr atom in the nanocomposite material.
[0052] (3) Microscopic morphology investigation The samples were scanned using a JEM-F200 transmission electron microscope (JEOL) and subjected to STEM energy-scattering X-ray (STEM-EDX) elemental mapping image scanning and high-angle annular dark field (HADDF) imaging. Figure 7 The nanocomposite material sample (HNTs@NaYF4:Pr 3+ ) high-resolution transmission electron microscopy element distribution map. Among them, Si, Al, and O elements are distributed on the nanotubes, which is consistent with the original chemical composition of halloysite nanotubes. Na, Y, F, and Pr elements are distributed on the nanoparticles generated on the surface of the nanotubes, which is consistent with the original chemical composition of NaYF4:Pr 3+Since the atomic coefficient of Pr is significantly higher than that of Si, Al, and O in nanotubes, Figure 8 The newly generated nanoparticles are shown in the HADDF graph to be significantly brighter than the nanotubes. Figure 8 It shows that the size of the newly generated nanoparticles ranges from 50 to 120 nm.
[0053] (4) Investigation of photophysical properties The fluorescence emission spectrum of the nanocomposite material was tested using an Andor SR500i X-ray source. The sample material was fixed on a special mold, and the instrument parameters were adjusted to a standard current of 30 mA and a standard voltage of 40 kV for irradiation. The photoluminescence intensity and wavelength were collected using an optical fiber detection collector. The results are shown in Figure 2. Fig. 9 The sample has an emission peak near 405nm, showing typical X-ray radiation luminescence material properties.
[0054] The light yield of the prepared material was tested according to the reference (Nano Res. 2023, 16, 3339-3347). A LuAG:Ce type scintillator standard with a light yield (LY) of 25000 photos / MeV was used as a reference to calculate the light yield of the nanocomposite materials in Examples 1-3. The data show that the light yields of the nanocomposite materials in Examples 1-3 are 12000, 7600 and 5600 photos / MeV, respectively. The light yield of the nanocomposite material in Example 1 is higher than that of the commercial scintillator BGO (8500 photos / MeV).
Claims
1. A method for preparing a nanocomposite material having good water dispersibility and X-ray radiation luminescence performance, characterized in that: The steps include: (1) taking halloysite nanotubes, adding them into water to prepare a nanosuspension, then adding disodium ethylenediaminetetraacetate, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-hydroxybenzotriazole and N,N-diisopropylethylamine, stirring for reaction, performing a first centrifugation after the reaction is completed, discarding the lower layer of precipitate, taking the upper layer of suspension, performing a second centrifugation, collecting the precipitate, and drying under reduced pressure to obtain modified halloysite nanotubes; (2) The modified halloysite nanotubes described in step (1) are added to water to form a nanosuspension, and then sodium nitrate, yttrium nitrate hexahydrate, praseodymium nitrate hexahydrate and ammonium fluoride are added. The pH value is adjusted to weak acidity with nitric acid, and the suspension is transferred to a hydrothermal synthesis reactor, heated for reaction, cooled to room temperature, centrifuged to collect the precipitate, and dried under reduced pressure to obtain the nanocomposite material.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of disodium ethylenediaminetetraacetate to halloysite nanotubes is (0.5-4):1, the mass ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to halloysite nanotubes is (0.5-4):1, the mass ratio of 1-hydroxybenzotriazole to halloysite nanotubes is (0.5-4):1, and the mass ratio of N,N-diisopropylethylamine to halloysite nanotubes is (0.5-4):
1.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of disodium ethylenediaminetetraacetate to halloysite nanotubes is (1-2):1, the mass ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to halloysite nanotubes is (1-2):1, the mass ratio of 1-hydroxybenzotriazole to halloysite nanotubes is (0.5-1.5):1, and the mass ratio of N,N-diisopropylethylamine to halloysite nanotubes is (0.5-1.5):
1.
4. The preparation method according to claim 1, characterized in that: In step (1), the reaction time is 24 to 72 hours, the reaction temperature is 15 to 50°C, the first centrifugation speed is 500 to 2000 rpm, and the second centrifugation speed is 5000 to 8000 rpm.
5. The preparation method according to claim 1, characterized in that: In step (1), the reaction time is 30 to 60 hours and the reaction temperature is 25 to 35°C.
6. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the sodium nitrate to the modified halloysite nanotube is (0.2-2):1; the mass ratio of the yttrium nitrate hexahydrate to the modified halloysite nanotube is (1-5):1; the mass ratio of the praseodymium nitrate hexahydrate to the modified halloysite nanotube is (0.1-0.5):1; the mass ratio of the ammonium fluoride to the modified halloysite nanotube is (0.5-3):
1.
7. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the sodium nitrate to the modified halloysite nanotube is (0.4-1):1; the mass ratio of the yttrium nitrate hexahydrate to the modified halloysite nanotube is (2-4):1; the mass ratio of the praseodymium nitrate hexahydrate to the modified halloysite nanotube is (0.2-0.4):1; the mass ratio of the ammonium fluoride to the modified halloysite nanotube is (0.8-2):
1.
8. The preparation method according to claim 1, characterized in that: In step (2), the pH value is 4-6, and the hydrothermal reaction temperature is 150-200°C.
9. The preparation method according to claim 1, characterized in that: In step (2), the pH value is 4.5-5.5, and the hydrothermal reaction temperature is 170-190°C.
10. The nanocomposite material obtained by the preparation method according to any one of claims 1 to 9.